The Friday Night Club - Lundberg, Sofia, 1974-; Richman, Alyson; Rose, M. J., 1953- (Berkley, 2023)
"While men have long been credited with producing the first abstract paintings, the true creator was actually a woman - Swedish artist Hilma af Klint, who was inspired by her mystic visions. Acclaimed authors Sofia Lundberg, Alyson Richman, and M.J. Rose bring her story to life in this groundbreaking novel. Early 1900s: The world belongs to men, and the art world in Stockholm, Sweden, is no different, until Hilma af Klint brings together a mysterious group of female painters and writers-Anna, Cornelia, Sigrid, and Mathilda-to form their own emotional and artistic support system. The members of the Friday Night Club find themselves thrust into uncharted territory when Hilma and her best friend, Anna, begin dabbling in the occult, believing that through séances they can channel unseen spirits to help them achieve their potential as artists. "The Five," as Hilma referred to them, was a group of immensely talented, fascinating women whose lives and work were cast into obscurity...until now. The Present: Over a century later, an associate curator at the Guggenheim Museum, Eben Elliot, brings the Hilma af Klint show to New York where he uncovers questions about the Five and how the modern day art world is funded, which puts him in a precarious position both emotionally and professionally, as he witnesses how history can be manipulated. The Friday Night Club is an illuminating historical novel that explores destiny, passion, and the threads that connect five women as they challenge artistic and societal traditions"--